2010
DOI: 10.1177/0022343309350013
|View full text |Cite
|
Sign up to set email alerts
|

Socio-psychological implications for an occupying society: The case of Israel

Abstract: Although prolonged occupation of a nation is no longer a common phenomenon, where it does exist, it bears harsh implications for all parties involved. This article examines the socio-psychological implications of occupation on the occupying society, using the case of the Israeli occupation of the Palestinian territories of the West Bank and Gaza Strip since 1967 as an example. The article first delineates the concept of occupation from a socio-psychological perspective, which supplements the legal-formal aspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 60 publications
1
34
0
Order By: Relevance
“…Previous studies suggested that societies tend to morally disengage from their past or currently unacceptable wrongdoing (Bandura, 1999;Coman et al, 2014) thus minimizing its perceived negative consequences (Leidner et al, 2010) and reducing moral emotions (Lickel et al, 2011;Wohl & Branscombe, 2008). However, to cope with the challenges of an ongoing occupation, the occupying society also constructs a system of sociopsychological coping mechanisms, including denial of the occupation and various justifications for its continuation (Halperin et al 2010). We suggest that such denial creates a strong barrier to peaceful conflict resolution by ending the occupation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that societies tend to morally disengage from their past or currently unacceptable wrongdoing (Bandura, 1999;Coman et al, 2014) thus minimizing its perceived negative consequences (Leidner et al, 2010) and reducing moral emotions (Lickel et al, 2011;Wohl & Branscombe, 2008). However, to cope with the challenges of an ongoing occupation, the occupying society also constructs a system of sociopsychological coping mechanisms, including denial of the occupation and various justifications for its continuation (Halperin et al 2010). We suggest that such denial creates a strong barrier to peaceful conflict resolution by ending the occupation.…”
Section: Discussionmentioning
confidence: 99%
“…Because it involves the acceptance of responsibility for harm committed by the ingroup (Branscombe, ), the experience of group‐based guilt has been found to lead to support for reparations or compensation to the outgroup affected by this harm (e.g., Branscombe & Doosje, ). Here lies its importance in the context of resolving intergroup conflict, but the induction of guilt may be extremely hard to achieve because it threatens the group's positive image (Halperin, Bar‐Tal, Sharvit, Rosler, & Raviv, ; Wohl & Branscombe, ).…”
Section: Emotion Regulation In Intractable Conflictsmentioning
confidence: 99%
“…As we have described in an elaborate analysis of that situation (see Halperin, Bar-Tal, Sharvit, Rosler, & Raviv, 2010), given that most Israelis wish to preserve the status quo, they rationalize and justify the occupation in a way that portrays it as legitimate, and as such, it prevents them from feeling guilty for actions conducted in the name of the occupation. As we have described in an elaborate analysis of that situation (see Halperin, Bar-Tal, Sharvit, Rosler, & Raviv, 2010), given that most Israelis wish to preserve the status quo, they rationalize and justify the occupation in a way that portrays it as legitimate, and as such, it prevents them from feeling guilty for actions conducted in the name of the occupation.…”
Section: Guilt In the Name Of One's Groupmentioning
confidence: 99%
“…This leads to a paradoxical situation in which groups are proud of their perceived moral behavior regarding contemporary or historical wrongdoings. For years, the Israeli mainstream defined it as an enlightened occupation (in Hebrew, Kibush Naor), and the main theme has been that the Palestinian's situation would have been much worse had they been under the sovereignty of other Arab countries (see Halperin, Bar-Tal, Sharvit, Rosler, & Raviv, 2010). Similarly, many Israelis are proud of the way Israel treats Palestinians in the occupied territories.…”
Section: Pride and Humiliation In The Intergroup Contextmentioning
confidence: 99%